(3QaY TCf GdMHTGfs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd HYV GdCLfGS Ydi HYV gPG cJGH hVYJg ai aVd GdMHT eQJHkG Ydi ebOeI hSHY aUhd hNGJeg hSejJg QaY TCf GdMHTGf s
(3BNQgG (B:s
(3EPG Sde ef UdGJg bGd (B: (3SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf , hGdMeO ddg QH GdYGdejf gPG BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdCOHs